Parking Study and Willingness to Pay for Vehicle Parking: The Case in Iligan City, Philippines - Trinidad, Metodia; Cantila, Kenny (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2019)
Parking is one of the important components in a transportation system, as a vehicle must park at every travel destination. When parking supply in an area is less than the parking demand, this may result to parking problem. Iligan City has been experiencing this kind of problem, as more travellers choose to use private vehicles rather than by public utility jeepneys (PUJs), thus, increasing the demand for parking spaces. This study is conducted to determine the parking adequacy in order to find appropriate solutions to parking problems in the study areas. The methods used include: street inventory for parking supply, plate number method for parking demand and random survey for the willingness to pay. The results of the parking study show that, in general, the average parking index in the study areas is 1.44 during weekdays and 1.18 during weekends. This means that the parking spaces are beyond capacity at a particular time, thus, prospective parkers may have to look for other areas to park their vehicle. But when available parking space is farther from the intended destination, some may resort to illegal parking. The results of the survey for the willingness to pay for parking use show that seventy nine percent (79%) of the total respondents is willing to pay against twenty one percent (21%) who responded negatively. The City Government of Iligan may utilize the results of this survey to enforce Article XV of the New Traffic Code of the City that designates pay parking areas around the City.